2008
DOI: 10.1021/ja804071h
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Growth of ZnO in Organic Solvents - an in Situ Study

Abstract: ZnO is a metal oxide material which possesses versatile properties and applications. Therefore, the target-oriented preparation of ZnO has become a major issue. Many preparation techniques involve bottom-up methods from precursor solutions. In the current contribution, a special precursor system is described that enables a fine-control of kinetic parameters for the nucleation and growth of ZnO in various organic solvents. A large variety of analytical techniques could be applied in an in situ fashion to probe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 61 publications
2
85
0
1
Order By: Relevance
“…The reaction of the Zn 4 O 4 precursors with an equimolar amount of water (see Scheme 1 ) and the resulting nucleation and growth of ZnO was reported recently in a detailed in situ study. [ 31 ] Because the emerging inorganic particles were not stabilized by surfactants, as expected, it was observed that the growth period of ZnO is very short due to rapid precipitation of ZnO. [ 31 ] When the reaction is performed in the presence of a suitable surfactant, colloidal stabilization occurs and one obtains transparent solutions.…”
Section: Shape Anisotropy Infl Uencing Functional Properties: Trigonamentioning
confidence: 87%
See 2 more Smart Citations
“…The reaction of the Zn 4 O 4 precursors with an equimolar amount of water (see Scheme 1 ) and the resulting nucleation and growth of ZnO was reported recently in a detailed in situ study. [ 31 ] Because the emerging inorganic particles were not stabilized by surfactants, as expected, it was observed that the growth period of ZnO is very short due to rapid precipitation of ZnO. [ 31 ] When the reaction is performed in the presence of a suitable surfactant, colloidal stabilization occurs and one obtains transparent solutions.…”
Section: Shape Anisotropy Infl Uencing Functional Properties: Trigonamentioning
confidence: 87%
“…[ 31 ] Because the emerging inorganic particles were not stabilized by surfactants, as expected, it was observed that the growth period of ZnO is very short due to rapid precipitation of ZnO. [ 31 ] When the reaction is performed in the presence of a suitable surfactant, colloidal stabilization occurs and one obtains transparent solutions. The results obtained by the latter experiments will be discussed only shortly because they have to be seen as references for the new synthesis approach towards colloidal ZnO nanoparticles described in Section 2.2.…”
Section: Shape Anisotropy Infl Uencing Functional Properties: Trigonamentioning
confidence: 87%
See 1 more Smart Citation
“…[37][38][39] All other chemicals were obtained from chemical suppliers and were purified and/or dried prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…7,8,10 Sol-gel processes, and in particular reaction pathways in organic solvents have become increasingly attractive in comparison to aqueous routes, as it is easier to tune the nanoparticle size, shape and crystallinity. 11 With available knowledge of chemical reaction pathways, 4,12 in situ small angle X-ray scattering (SAXS) and UV-vis spectroscopy have given access to the nucleation and growth behaviour, 3,4,7,8,[13][14][15][16] however with somewhat contradictory ripening rates and growth models. 13 Theoretical attempts to describe ZnO nanoparticle nucleation have involved molecular dynamics (MD) simulations 17 knowledge, besides the Spanhel model, all other experimental and theoretical approaches have so far assumed the nucleation of dense particles, which further grow or agglomerate.…”
Section: Introductionmentioning
confidence: 99%